Characterization of greedy bases in Banach spaces - Berná, Pablo M.; Blasco, Óscar (Journal of approximation theory, 2017)
We shall present a new characterization of greedy bases and 1-greedy bases in terms of certain functionals defined using distances to one dimensional subspaces generated by the basis. We also introduce a new property that unifies the notions of unconditionality and democracy and allows us to recover a better dependence on the constants.